Comparative analysis of baby food labelling in Hungary and in Romania: Consumers' perspective - Noémi Hajdú; Katalin Lipták; Zsuzsa Săplăcan (Amfiteatru Economic Journal, 2018)
Baby food represents a growing segment of the food industry; the baby food labelling issues affect more and more mothers who want to make better and safer nutritional choices. In a continuously improving food labelling regulation environment consumer studies regarding the baby food labelling are very limited. Present article has an exploratory nature and aims to find specific patterns of baby food buying behaviour and labelling preference in Romania and Hungary, and also to reveal the behavioural similarities and differences between the two countries. To meet this aim, a questionnaire-based quantitative research was designed. The sample consists of 993 mothers (590 from Hungary and 403 from Romania) with small children. Results show that there is a difference between Romanian and Hungarian mothers regarding the baby food buying habits. The profile of the mothers buying jarred baby food can be characterised by living in towns, with one or two children, and the propensity to give jarred baby food to their child is growing with their age. The mothers agree that the labels contain tiny, unreadable letters, disordered information, unknown expressions and bad translation. The Hungarian mothers pay more attention to the indication of allergen and to the ingredients list. The most important information cluster they seek on a label is related to product ingredients, the second is related to usage of baby food and the least important are the label design elements. The paper provides insightful results for the producers and policy-makers to improve the baby food label quality to help consumers to make better, healthier and safer food choices for their children.
Keywords: D18; M31; 330; food labelling; baby food; consumer law